Extensive Mucocutaneous Histiocytic Sarcoma raised from an Acute B Lymphocytic Leukemia: A Case Report at Hospital Mexico, Costa Rica - Rodríguez Pineda, Miguel A. (2017)
Histiocytic sarcomas are rare neoplasms with poor prognosis originating from histiocytic or dendritic cell clones and associated with haematological malignancies such as acute or chronic leukemias and lymphomas. We describe a case of a patient who developed a disseminated and extensive mucocutaneous histiocytic sarcoma during remission.